Assistance and Learning Strategies for Deaf Children - Nurazila Sari; Khamim Zarkasih Putro (JOYCED: Journal of Early Childhood Education, 2021)
This study aimed to find out how the strategies for mentoring and learning deaf children are. The current phenomenon about deaf children is that they have difficulty communicating or can be categorized as low in communication with other people because their vocabulary is lacking. In the world of education, there are still few people who understand the characteristics of deaf children. It was also found that one of the teachers at an extraordinary school was more understanding when communicating with children with disabilities, mental disorders, and others than communicating with deaf children. This data collection technique is through descriptive analysis, content analysis or content analysis, and concluding a literary method with the type of library research, namely the mentoring and learning strategy for deaf children. There is an inclusive school for each child according to their particular needs. All efforts are made to be served optimally by making various modifications and adjustments. Learning media that can be used for deaf children are visual stimulation media and auditory stimulation media.